Mos-only automation technique with an exemplary mos-only BP/LP agile filter design - (:unkn) unknown (Istanbul University, 2017)
In this work, a systematic of the automation in the result of the re-obtained small signal parameters based on SPICE and CADENCE-SPECTRE is presented for MOS-Only circuits. Accuracy of the re-obtained parameters was improved by re-formulating in the basis of SPICE and CADENCE-SPECTRE. Moreover, piece-wise polynomial regressive models are presented for gds, gm and Ids. Also, performance of the models is compared with conventional expressions. Success of the given MOS-Only design automation based on re-obtained small signal parameters is verified with an exemplary new agile filter.
Keywords: CADENCE-SPECTRE; MOS-Only; Polynomial; SPICE